Maskulinitas Dan Perempuan Pendukung Klub Sepakbola - Hairani Heryadi; Tia Lidarni; Ahmad Rudy Fardiyan (Jurusan Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Lampung, 2025)
Football broadcasts are a spectacle that is culturally associated with men. However, there are quite a number of women who are fans of football broadcasts. This research aims to understand the driving factors behind the culture of women watching football broadcasts, the motivations of women joining football fan clubs, and to identify the identity desired by female football fans. This study is qualitative research using observation and interviews. The results show that factors such as family, social environment, and elements within football broadcasts itself, such as players, costumes, and accessories, contribute to the emergence of the culture of women watching football. The motivation for women to join football fan clubs is based on interest in the clubs, influenced and supported by their family, as well as social environment, and a distinguishing factor from women in general. The identity desired by female members in football fan clubs is a manifest identity or a real identity. Keywords: Football fans women, Masculinity, Motivation, Identity,